2019
DOI: 10.18510/hssr.2019.7460
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Intellectual Capital and Competitive Advantage: A Case Study on the Hotel Industry in Bali Province, Indonesia

Abstract: Purpose: This study aims to examine the association between intellectual capital and competitive advantage in the hotel industry in Bali Province, Indonesia. The interrelationship between components of intellectual capital –human capital, relational capital, structural capital – were tested in this study, and testing was also carried out for the association of intellectual capital – represented by structural capital – with competitive advantage. Methodology: Data was collected using a self-administered q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
1
11
0
3
Order By: Relevance
“…In line with the explanations made, it is possible to say that the research hypothesis of "There is a positive, strong and significant relationship between intellectual capital and competitive advantage" has been confirmed. This positive and significant relationship between IC and CA supports the results of many studies such as Dahash and Al-Dirawi (2018), Taie (2014), Kamukama and Sulait (2017), Astuti et al (2019) and Assaf (2020). However, this significant relationship contradicts the research results of Elda et al (2021) and Crisnandani et al (2021).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In line with the explanations made, it is possible to say that the research hypothesis of "There is a positive, strong and significant relationship between intellectual capital and competitive advantage" has been confirmed. This positive and significant relationship between IC and CA supports the results of many studies such as Dahash and Al-Dirawi (2018), Taie (2014), Kamukama and Sulait (2017), Astuti et al (2019) and Assaf (2020). However, this significant relationship contradicts the research results of Elda et al (2021) and Crisnandani et al (2021).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, as a result of the study, it has been observed that intellectual capital has a positive and significant effect on competitive advantage. Similarly, Astuti et al (2019) conducted a study on 109 businesses in hotel industry in Bali, and it was found that there were positive and significant relationships between IC components and CA. In addition, it has been observed that structural capital has a statistically significant and positive effect on competitive advantage.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Intellectual capital is an intangible asset/organizational capital that is a collection of people, change processes, and consumers that provide competitive value for the company. [5]. Intellectual capital in the MSME sector is the main weapon in efforts to improve organizational performance.…”
Section: Introductionmentioning
confidence: 99%